Determinants Influencing Performance with Organizational Culture as a Moderating Variable - Fadhillah Octa Viola Ranti; Nasrizal; Nur Azlina (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
Based on the 2019 Health Profile report was found that the performance of Community Health Centers (Puskesmas) in Indonesia is still not optimal, also occurs at Puskesmas Minas in Siak Regency, Riau Province. This study aims to test and analyze the influence of Good Government Governance, Organizational Commitment, Internal Supervision, and Human Resource Quality on performance moderated by Organizational Culture. The data used are primary data sourced from questionnaires distributed to respondents. The data analysis technique used is SEM WarpPLS tool. The results of the study indicate that Good Government Governance, Organizational Commitment, Internal Supervision, and Human Resource Quality have an influence on performance. Organizational culture moderates the influence of Organizational Commitment and Internal Supervision on performance, while organizational culture is unable to moderate the influence of Good Government Governance and Human Resource Quality on performance.